Sex Differences in the Association Between Testosterone and Violent Behaviors - Assari, Shervin (Kowsar, 2014)
BACKGROUND: Research on the association between testosterone and violent behavior has provided conflicting findings. The majority of studies on the association between testosterone and antisocial-violent behaviors has used a clinical sample of severely violent individuals. These studies have mostly assessed males. OBJECTIVES: To study sex differences in the association between testosterone and violent behaviors in a community sample of young adults in the United States. PATIENTS AND METHODS: A longitudinal study of an inner city population on subjects aged from adolescence to adulthood was undertaken. Testosterone and violent behaviors were measured among 257 young adults with an average age of 22 years (range 21 to 23 years). We used regression analysis to test the association between testosterone and violent behaviors in male and female samples. RESULTS: There was a significant positive correlation between testosterone levels and violent behaviors among females, but not males. The association between testosterone levels and violent behaviors among females was significant, as it was above and beyond the effects of socio-economic status, age, education, and race. CONCLUSIONS: Our findings provide more information about the biological mechanisms for violent behaviors among young female adults. The study also helps us better understand sex differences in factors associated with violent behaviors in the community.